The impact of discrimination on mental health: implications for diagnosis and treatment - Tanhan, Fuat (The Bulletin of Legal Medicine, 2025)
The aim of this study is to examine, based on existing literature, the impact of social inequalities such as discrimination, marginalization, exclusion, and racism on individuals’ mental health. Discrimination, which is widespread in society, involves categorizing individuals into groups and assigning negative values to these groups, thereby reinforcing social inequalities. In particular, ethnic-based discrimination and racism contribute to the perception of certain individuals as occupying a lower status in society, increasing their exposure to stigmatization and exclusion. This, in turn, can lead to long-term psychological harm, posing a threat to individuals’ mental well-being. This study is a qualitative review research based on the systematic analysis of the relevant literature. Sources from the fields of psychology, psychiatry, and sociology, as well as diagnostic frameworks such as the DSM (Diagnostic and Statistical Manual of Mental Disorders) and ICD (International Classification of Diseases), were analyzed to assess the impact of discrimination on mental health. The study explores the relationship between discrimination and psychological conditions such as trauma, stress, and depression. The literature indicates that individuals subjected to discrimination and racism not only face social exclusion, labeling, and stigmatization, but also experience significant psychological difficulties, including anxiety, chronic stress, and depression. These effects are not confined to the individual level; they also contribute to the development of unhealthy and inequitable social structures. Inadequate social support further exacerbates psychological trauma. Moreover, diagnostic systems indirectly acknowledge that prolonged exposure to discrimination can lead to mental health disorders such as trauma, anxiety, and depression.The findings ...
Keywords: Discrimination; stigmatization; mental health; psychological assessment